Sleepiness and tiredness among doctors working in a tertiary hospital: Is it work related or is there underlying sleep disorders? / Imelda Kong Wei - Imelda , Kong Wei (2019)
Background Doctors who work in a tertiary hospital may frequently complain of sleepiness and tiredness. Majority of trainee doctors attribute these symptoms to the nature of their work having to do frequent night shifts or more than 24 hours work shift causing irregular sleep patterns and sleep deprivation. There are still limited data regarding sleep disorders among trainee doctors. Hence this study is to look at prevalence of obstructive sleep apnea (OSA) among doctors working in a tertiary hospital and also to identify if the sleepiness and tiredness is caused by undiagnosed OSA. Methods A prospective cross-sectional study is performed among doctors working in a tertiary hospital. All doctors recruited will be required to fill up the demographic data, STOP-Bang and Epworth Sleepiness Scale questionnaires. A wristwatch pulse oximetry will be given to each participant for home nocturnal oxygen saturation monitoring during sleep. Participant will have to wear the wristwatch to sleep overnight till the next day. Participant with oxygen desaturation index (ODI) of 10 and above will be offered a home sleep apnea testing (ApneaLink ResMed) to further evaluate the apnea hypoapnea index (AHI) for diagnosis of moderate to severe OSA. The STOP-Bang and ESS scores will be compared and correlate with data collected from the wristwatch pulse oximetry. iv Results Among the 130 of doctors recruited in this study, 39 (30%) found to have ODI of >5 and 19 subjects with ODI >10. Further evaluation with home sleep study showed 4 (3.1%) doctors had moderate OSA and 6 (4.6%) confirmed to have severe OSA. The prevalence of excessive daytime sleepiness (ESS >10) was 21% , tiredness (51%) and perception of inadequate sleep (41%). However there is no association between tiredness or sleepiness and OSA. The predictors of perception of having inadequate sleep were snoring (OR= 0.32; p=0.0015; 95%CI:0.12-0.8) and average sleep time during on-call (OR=0.57; p<0.001; 95%CI:0.4-0.8). While BMI and snoring were the significant predictors for OSA with odd ratio (OR) of 1.33 (p<0.001; 95% CI:1.14-1.55) and 5.14 (p=0.006; 95% CI:1.59-16.67) respectively. Conclusions Our study have shown significant prevalence of undiagnosed moderate to severe OSA among young doctors. Snoring and BMI are the only independent predictors for OSA. STOP BANG is not so accurate to predict OSA in young, healthy and non-obese population. ODI from high resolution oximetry is a good screening tool to detect OSA. We have demonstrated that shorter average sleep during on-call time as well as snoring are predictors of perception of always having inadequate sleep among the doctors participated in this study.